Assessment of Vietnam Coastal Wetland Vulnerability for Sustainable Use (Case Study in Xuanthuy Ramsar Site, Vietnam) - Nhuan, Mai Trong; Ngoc, Nguyen Thi Minh; Huong, Nghiem Quynh; Hue, Nguyen Thi Hong; Tue, Nguyen Tai; Ngoc, Pham Bao (Journal of Wetlands Ecology, 2009)
For sustainable use of coastal wetland ecosystems, vulnerability of the Xuan Thuy Ramsar site in the northern coast of Vietnam, an internationally important area for feeding and roosting of migratory water birds, is assessed. The assessment tools include 1) a geographical information system database, which describes physical, socio-economic, and environmental conditions; 2) spatial multi-criteria decision analysis, and 3) evaluating criteria by a pair-wise comparison method. Consequently, coastal vulnerability criteria were determined following three periods of a year with different density of migrating birds: the highest density period - from September to March of the following year; the average density period - April and from August to October; the lowest density period - the remain time in year. For each period, 5 levels of vulnerability (from 1-lowest to 5-highest level) were determined. High vulnerability level is concentrated in a great area, belonging to the ecological restored area and the south of communes Giao Thien, Giao Xuan; Low vulnerability level is distributed in communes of the buffer zone. Correspondingly to each vulnerability level, recommendations are given for the risk management, resource use, environment protection and human activities. Keywords: wetland, vulnerability, Ramsar site, hazard, sustainable use DOI: 10.3126/jowe.v2i1.1850 Journal of Wetlands Ecology, (2009) vol. 2, pp 1-16